Judges beyond politics in democracy and dictatorship lessons from Chile - Hilbink, Lisa (Cambridge studies in law and society, 2007)
A longitudinal case study of Chile that assesses competing hypotheses regarding judicial behavior in both democratic and undemocratic contexts, this book explores the relevance of regime-related factors, judges ' personal policy preferences, social class, and legal philosophy, but argues that institutional features grounded in the ideal of "apoliticism" best explain the persistent failure of Chilean judges to take stands in defense of rights and rule of law principles, before, during, and after the authoritarian interlude. Dr. Hilbink offers comparative examples to support broader theoretical claims about when judges will be willing and able to assert their independence against abuses of public power.